Taxonomy of eurymeline leafhoppers from Xizang, China (Hemiptera: Cicadellidae) with two new genera and three new species - Xue, Qingquan; Nyima, Tenzin; Da, Wa; Zhang, Yalin (Zootaxa, 2025)
The arboreal leafhopper subfamily Eurymelinae (excluding Macropsini) is revised for Xizang, China. Seven genera and eight species are recognized, including two new genera (Xizangocerus gen. nov. and Yarlungocerus gen. nov.) and three new species (Xizangocerus gyirongensis sp. nov., X. chayuensis sp. nov. and Yarlungocerus linzhiensis sp. nov.). A key to species of Xizang Eurymelinae (excluding Macropsini) is provided.